SAT0452 DIFFERENT PROFILE OF RISK OF FRACTURE IN PATIENTS TREATED WITH ANTI-OSTEOPOROTIC DRUGS IN ITALY USING A NEW ALGORITHM. (2nd June 2020) - Adami, G.; Fassio, A.; Giollo, A.; Orsolini, G.; Viapiana, O.; Gatti, D.; Rossini, M.
Abstract : Background: A new algorithm for management of patients at low, high and very high risk of osteoporotic fractures has been recently proposed, has been also recommended treating those patients at very high risk of fracture with bone anabolics (1). A similar treatment algorithm has been applied in Italy since 2015, when the "Nota 79", that regulates the reimbursability for osteoporosis medications, has been developed by the Italian Agency for Drugs (AIFA) (2). Objectives: In the present study, using a new mathematical and computerized algorithm, we seek to investigate the profile of risk of fracture of patients starting treatment with different anti-osteoporotic medications in Italy. Methods: We retrospectively analyzed the 10-year risk of major osteoporotic fracture calculated with the DeFRAcalc79 tool in postmenopausal women aged over 50 years that were initiating an anti-osteoporotic treatment (fully reimbursed according to the Nota 79). DeFRAcalc79 is a new web-based fracture risk-assessment tool (https://defra-osteoporosi.it ) that arithmetically adjusts the risk based on the integration of multiple risk factors contemplated by the AIFA's Nota 79, including: demographic and anthropometric data, femoral and/or lumbar spine BMD T-score, family history of femoral or vertebral fractures, number and site of previous osteoporotic fracture (including vertebral, femoral, and nonvertebral nonfemoral fractures), glucocorticoid treatment (> 3 or > 12 months, ≥5 mg prednisone or equivalent), adjuvant hormone therapy for breast or prostate cancer, and comorbidities that increase the risk (rheumatoid arthritis and other connective tissue diseases, chronic obstructive pulmonary disease, inflammatory bowel diseases, Parkinson's disease, multiple sclerosis, HIV infection, diabetes, or severe physical handicap). Results: We retrieved data for 10, 235 women prescribed with an anti-osteoporotic treatment. Figure 1 shows the mean 10-year fracture risk estimated with DeFRAcalc79 tool at the time of the treatment initiation. Teriparatide users had the highest 10-year risk of fracture (67.4% Standard Deviation [SD] 21.5%). We found that in 2, 231 patients starting denosumab, the 10-year baseline risk of fracture was 38.5%, SD 22.8%. In 5, 759 patients initiating alendronate was 25.7%, SD 15.3% and in patients initiating risedronate was 27.9%, SD 26.9%. Patients prescribed with zoledronic acid had a mean 10-year risk of fracture of 35.6%, SD 21.6. P values between means were all <0.01. Conclusion: The risk of fracture of Italian post-menopausal women initiating different anti-osteoporotic medications varies significantly. Teriparatide is prescribed to patients with greater risk of fracture. The Nota 79 correctly individuates patients at very high risk of fracture that merit treatment with a bone anabolic. Denosumab and zoledronic acid are prescribed to patients with a greater risk of fracture compared to oral bisphosphonates. DeFRAcalc79 is a useful and practical tool for the integrated evaluation of the profile of risk of fracture. References: [1]Kanis JA et al. Algorithm for the management of patients at low, high and very high risk of osteoporotic fractures. Osteoporos Int 2019 31:1–12. https://doi.org/10.1007/s00198-019-05176-3 [2]Adami G et al. Comments on Kanis et al.: Algorithm for the management of patients at low, high, and very high risk of osteoporotic fractures. Osteoporos Int. 2020. doi: 10.1007/s00198-020-05302-6. [Epub ahead of print] Disclosure of Interests: Giovanni Adami: None declared, Angelo Fassio Speakers bureau: Angelo Fassio reports personal fees from: Abiogen and Novartis, outside the submitted work., Alessandro Giollo: None declared, Giovanni Orsolini: None declared, Ombretta Viapiana: None declared, Davide Gatti Speakers bureau: Davide Gatti reports personal fees from Abiogen, Amgen, Janssen-Cilag, Mundipharma, outside the submitted work., Maurizio Rossini Speakers bureau: AbbVie, Abiogen, Amgen, BMS, Eli-Lilly, Novartis, Pfizer, Sanofi, Sandoz and UCB